The development of ozone-filtration using green mussels shells for laundry wastewater treatment - Amira Liontina Ichlasia; Azzahra Shakayla Althafunnisa; Cheryl Sheridia; Kinanthy Ayudia Putri Nugroho; Zameera Adelia; Himmatul Ulya; Putri Dyah Astari; Rifqi Ahmad Baihaqi (Journal of Bioresources and Environmental Sciences, 2025)
This study explores the potential of green mussel shells as a filtration medium for treating laundry wastewater. The research evaluated the effects of ozonation as a pre-treatment step and compared two filtration reactors, reactor one (R1) without green mussel shells and reactor two (R2) using green mussel shells. In this filtration system, hydrostatic force is used due to its reliability in determining the pressure difference between the upstream and downstream sides of the reactors. Treated wastewater samples were collected every 5 minutes to be analyzed. Several important water quality parameters are monitored, including pH, chemical oxygen demand (COD), and dissolved oxygen (DO). The odor and color of the laundry wastewater were also observed. Results showed the effectiveness of green mussel shells in improving wastewater quality, particularly in neutralizing pH, reducing COD, and increasing DO. The results of linear regression calculations showed that in R2, the pH decreased by around 26%, the COD concentration decreased by 76%, and the greater increase in DO was 118% from the concentration without treatment. This research showed that green mussel shells in R2 have the potential to be used as a filtration element to treat laundry wastewater as a sustainable solution, addressing both environmental pollution and water quality challenges.